The Effect of Social Media Marketing Activities on Purchase Decisions Mediated by Perceived Quality - Amrullah, M.Faris; Riyoko, Sisno; Widiastuti, Anna (Journal of Social Science and Education Research, 2024)
This study aims to analyze the influence of Social Media Marketing Activities (SMMA) on consumer purchase decisions, focusing on the role of Perceived Quality as a mediating variable. In the context of Pempek Yuk Paka culinary UKM in Banyumanis, Jepara. The results of the study showed that SMMA had no positive and insignificant effect on purchase decisions. In addition, quality perception is proven to function as a mediator that strengthens the relationship between SMMA and purchasing decisions.